Deficiency of Myeloid Pfkfb3 Protects Mice From Lung Edema and Cardiac Dysfunction in LPS-Induced Endotoxemia - Jiean Xu (Frontiers in Cardiovascular Medicine, 2021)
Sepsis, a pathology resulting from excessive inflammatory response that leads to multiple organ failure, is a major cause of mortality in intensive care units. Macrophages play an important role in the pathophysiology of sepsis. Accumulating evidence has suggested an upregulated rate of aerobic glycolysis as a key common feature of activated proinflammatory macrophages. Here, we identified a crucial role of myeloid 6-phosphofructo-2-kinase/fructose-2,6-bisphosphatase 3 (Pfkfb3), a glycolytic activator in lipopolysaccharide (LPS)-induced endotoxemia in mice. Pfkfb3 expression is substantially increased in bone marrow derived macrophages (BMDMs) treated with LPS in vitro and in lung macrophages of mice challenged with LPS in vivo. Myeloid-specific knockout of Pfkfb3 in mice protects against LPS-induced lung edema, cardiac dysfunction and hypotension, which were associated with decreased expression of interleukin 1 beta (Il1b), interleukin 6 (Il6) and nitric oxide synthase 2 (Nos2), as well as reduced infiltration of neutrophils and macrophages in lung tissue. Pfkfb3 ablation in cultured macrophages attenuated LPS-induced glycolytic flux, resulting in a decrease in proinflammatory gene expression. Mechanistically, Pfkfb3 ablation or inhibition with a Pfkfb3 inhibitor AZ26 suppresses LPS-induced proinflammatory gene expression via the NF-κB signaling pathway. In summary, our study reveals the critical role of Pfkfb3 in LPS-induced sepsis via reprogramming macrophage metabolism and regulating proinflammatory gene expression. Therefore, PFKFB3 is a potential target for the prevention and treatment of inflammatory diseases such as sepsis.